Diligence and tradition in the "facilitation of interpretation" of Sheikh Mohammed bin Yusuf Tfayyesh - Al- Battashi, Hilal Khalfan Mohammed (Journal of Islamic Sciences, 2019)
This study sheds light on the approach of the scholar Amahd ibn Yusuf al- Atfish in ijtihad and tradition, through his interpretation of the Holy Quran, which he called "facilitating interpretation." The study was based on scientific methods, namely the inductive method and the deductive approach. , And graduation conversations, and so on. The study concluded that Sheikh Aftish had opinions and applications related to diligence and tradition. He dealt with many issues related to the process of ijtihad, and he had corrections and calamities, not only what he quoted from the scholars, but was correct and likely and cite and cite. The study has recommended. The study recommended that researchers in the fundamentals of jurisprudence should research the jurisprudence of Ibadi jurisprudence, extract the fundamental issues, collect the scattered ones, study them in depth, and show the curricula of fundamentalist scholars who do not have independent fundamentalist books.